The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.bjc.6602325
|View full text |Cite
|
Sign up to set email alerts
|

Invasive characteristics of human prostatic epithelial cells: understanding the metastatic process

Abstract: Prostate cancer has a predilection to metastasise to the bone marrow stroma (BMS) by an as yet uncharacterised mechanism. We have defined a series of coculture models of invasion, which simulate the blood/BMS boundary and allow the elucidation of the signalling and mechanics of trans-endothelial migration within the complex bone marrow environment. Confocal microscopy shows that prostate epithelial cells bind specifically to bone marrow endothelial-to-endothelial cell junctions and initiate endothelial cell re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 39 publications
3
78
1
Order By: Relevance
“…Binding to laminin, type IV and type V collagens is mediated by b 1 and b 4 integrins, whereas bin ding to hyaluronan, fibronectin, type I collagen and cellular migration is mediated by b 1 integrins and CD44 [44,[46][47][48][49]. Understanding the process of secondary site binding and endothelial transmigration in PCa has been facilitated by the development of co-culture models using human BMS and primary PECs and PEC lines [27,39] and the establishment of prostate epithelial colonies in human BMS [50,51]. These models have demonstrated that cell-matrix binding depends fundamentally on the b 1 integrin component of the integrin-binding mechanism.…”
Section: Distal Attachment and Tumour Cell Transmigration Through Thementioning
confidence: 99%
“…Binding to laminin, type IV and type V collagens is mediated by b 1 and b 4 integrins, whereas bin ding to hyaluronan, fibronectin, type I collagen and cellular migration is mediated by b 1 integrins and CD44 [44,[46][47][48][49]. Understanding the process of secondary site binding and endothelial transmigration in PCa has been facilitated by the development of co-culture models using human BMS and primary PECs and PEC lines [27,39] and the establishment of prostate epithelial colonies in human BMS [50,51]. These models have demonstrated that cell-matrix binding depends fundamentally on the b 1 integrin component of the integrin-binding mechanism.…”
Section: Distal Attachment and Tumour Cell Transmigration Through Thementioning
confidence: 99%
“…Invasion assays were conducted according to Hart et al 16 Basically 1 Â 10 5 cells in 0.25 ml RPMI 1640-0.1% fatty acid free BSA were seeded into cell culture inserts (8 mm pore size) coated with phenol red free MatrigelÔ diluted 1 : 25 with phenol red free RPMI 1640 medium. The inserts were placed in a 24 well plate containing 1 ml of RPMI 1640 (w/o phenol red)-0.1% fatty acid free BSA-10 mM HEPES over tissue culture plastic (TCP) or human bone marrow stroma (BMS).…”
Section: Invasion Assaymentioning
confidence: 99%
“…A variation of the invasion co-cultures described by Hart et al (2005) was used. Briefly, FluoroBlok cell culture inserts (8 mm) coated with Matrigel diluted 1 : 25 with phenol red free RPMI 1640 medium, were placed in a 24-well plate containing 1 ml of RPMI 1640 (w/o phenol red)/0.1% fatty acid free (FAF) BSA/ 10 mM HEPES with either tissue culture plastic (TCP), BMS, mBMAd or lipids in the base.…”
Section: Invasion Assaymentioning
confidence: 99%